Operator tematyczny jako wobec jego historycznej funkcji porównawczej - Kleszczowa, Krystyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article discusses the inspirations which linguistics may draw from the semantic-syntactic research trend in the modern language. Obviously it explores only a model and a point of reference, for it is impossible to faithfully transfer methods used by synchronic linguistics to the study of historical material. This year saw the publication of Magdalena Danielewiczowa’s work entitled „Aspekt tematyczny w strukturze informacyjnej wypowiedzi. Rozszerzanie i integracja wiedzy” [“The Thematic Aspect in the Informational Structure of Utterances. How Knowledge is Made Broader and Integral”], whose author suggests that the thematic-rhematic structure should be extended to cover expressions which indicate the aspect which is expressed by the theme – we are dealing with the exponents of the thematic aspect (thematisers). A thematiser, which in reference to the Polish language Magdalena Danielewiczowa posits in the first place, is jako, a functional expression which historically occupied the first place among the exponents of comparison. Which elements are shared by jako in both functions? In typical comparative constructions (gradational and non-gradational ones) we compare two objects, A and B, and we compare them in reference to some property (Z). In a construction in which jako performs the function of a thematiser, we characterise A (theme) in order to say something about A in comparison to itself (A1), although in a different role; obviously we do this also due to the property Z: Jan (A) jako urzędnik (Z) jest skrupulatny, ale poza urzędem Jan (A1) jest strasznym bałaganiarzem. [Jan (A) is diligent as an employee (Z), but outside his office-related work Jan (A1) is a terribly messy person.] In both cases we may speak about characterisation, on the one hand by means of seeking a similarity between A and B, and, on the other hand, by means of attributing some property to A. In the further part of her discussion, the author attempts to explain why the comparative jako was transformed into jak (the disappearance of ~o), and how jako in turn, prevailed, in the function of a thematiser, in the competition with other functors.
Keywords: diachronic linguistics; thematic-rhematic structure; comparative constructions; thematic aspect